2007
DOI: 10.1080/14767050701288218
|View full text |Cite
|
Sign up to set email alerts
|

Maternal–fetal transport kinetics of methotrexate in perfused human placenta:In vitrostudy

Abstract: We report for the first time that the transport of methotrexate from maternal to fetal circulation is not negligible in human placenta at term. It is reasonable to assume that a direct risk for the fetus from methotrexate use in pregnancy cannot be excluded, and caution is warranted when it is used in emergency clinical situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Although chemotherapy is considered safe after the fi rst trimester, only few studies have investigated the long-term eff ect of in utero exposure. Some chemotherapeutic agents are known to cross the placental barrier such as cisplatin (16), cyclophosphamide (17), doxorubicine (18) and methotrexate (19). Methotrexate has been associated with malformations of the central nervous system, skeletal, gastrointestinal, and cardiac malformations, and even fetal death (20).…”
Section: Treatment Optionsmentioning
confidence: 99%
“…Although chemotherapy is considered safe after the fi rst trimester, only few studies have investigated the long-term eff ect of in utero exposure. Some chemotherapeutic agents are known to cross the placental barrier such as cisplatin (16), cyclophosphamide (17), doxorubicine (18) and methotrexate (19). Methotrexate has been associated with malformations of the central nervous system, skeletal, gastrointestinal, and cardiac malformations, and even fetal death (20).…”
Section: Treatment Optionsmentioning
confidence: 99%
“…The lobular perfusion technique has been used by our research group for the study of maternal-fetal exchange of diverse groups of drugs, including anticancer agents [9][10][11]. This method has the unique advantage of exploring transport across the placental membrane, under controlled experimental conditions, and independent of maternal and fetal hemodynamic and metabolic influences.…”
Section: Introductionmentioning
confidence: 99%
“…MTX caused increasing apoptotic cells, delaying in Sphase, decreasing the number of mitotic cells and reduction in the number of cells of the foetuses of developing zebrafish (Lee et al, 2012). Also, it was found in the umbilical blood and placenta of a woman who received MTX causing foetal chromosomal aberrations (Al-Saleh et al, 2007). Studies in rats, mice, and rabbits revealed embryotoxicity and teratogenicity (Al-khateeb et al, 2014).…”
mentioning
confidence: 99%